Rurality representation and changes in rural tourism destination - Xueting Hong; Zhenfang Huang; Xinyi Li; Yechen Zhang (PLoS ONE, 2026)
Representation of rurality plays a crucial role in developing rural tourism. However, the connotations of rural destinations and how such representations shift across different social contexts remains unclear. This study aims to examine the rurality of, and changes in, rural tourism destinations through the lens of social representation theory. Semi-structured interviews were conducted with 50 residents and 17 tourists from rural destinations in Nanjing, China. We identified three core dimensions of rurality representation in these destinations: material, social, and cultural. From these, six primary categories emerge: the natural environment, settlement architecture, production and daily life, interpersonal relationships, folk customs and festivals, and spiritual orientation. The findings indicate that the representation of rurality in rural tourism destinations has evolved from an agriculture-centred to a tourism-centred focus. We confirm that rurality is socially constructed and varies according to social background. Rural tourism development should consider the nuanced connotations of rurality and adopt a dynamic perspective to foster high-quality growth in the sector.